1997
DOI: 10.1007/s002800050608
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle effects of antifolate antimetabolites: implications for cytotoxicity and cytostasis

Abstract: These results demonstrate that the distinct endpoints of GARFT and TS inhibition are preceded by distinct cell cycle and metabolic alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 16 publications
7
33
0
2
Order By: Relevance
“…Drugs interacting at different sites in the cell cycle might potentiate the therapeutic response. In this study, FACS analysis demonstrated that pemetrexed caused an S-phase arrest, as previously detected in different tumour cell lines (Tonkinson et al, 1997(Tonkinson et al, , 1999Giovannetti et al, 2005). In contrast, enzastaurin alone increased the percentage of cells in the G1 phase, whereas in the combination the cells accumulated in G2/M phase.…”
Section: Discussionmentioning
confidence: 51%
“…Drugs interacting at different sites in the cell cycle might potentiate the therapeutic response. In this study, FACS analysis demonstrated that pemetrexed caused an S-phase arrest, as previously detected in different tumour cell lines (Tonkinson et al, 1997(Tonkinson et al, , 1999Giovannetti et al, 2005). In contrast, enzastaurin alone increased the percentage of cells in the G1 phase, whereas in the combination the cells accumulated in G2/M phase.…”
Section: Discussionmentioning
confidence: 51%
“…Secondly, raltitrexed and MTX exert their cytotoxic effects by blocking cells in the S phase. 1,23,24) Thus, MTX might enhance the cytotoxicity of raltitrexed by blocking cells in the Sphase, in which the cells are most sensitive to raltitrexed.…”
Section: Discussionmentioning
confidence: 99%
“…Pemetrexed is a new multitarget antifolate metabolite that acts on the enzymes thymidylate synthase (TS), dihydrofolate reductase (DHFR) and glycinamide ribonucleotide formyl transferase (GARFT), 4 thereby depleting nucleotide pools and blocking DNA synthesis. 5,6 Pemetrexed is transported into the cell via the reduced folate carrier and the folate binding protein. After being transported into the cell, Pemetrexed is polyglutamated by the enzyme folyl-polyglutamyl synthase.…”
Section: Introductionmentioning
confidence: 99%